Dinamika Paket Gelombang Elektron yang Menerobos Penghalang Trapesium dengan Ketebalan Nanometer - Maharati Hamida; Khairurrijal Khairurrijal; Mikrajuddin Abdullah (Jurnal Matematika & Sains, 2006)
A simulation of the dynamics of electrone wave packet tunneling through a potential barrier in a MOS (metal-oxide-semiconductor) diode was performed by solving the time-dependent SchrÃ¶dinger equation using the finite difference method. The wave packet is initially located in the semiconductor layer then moves toward to the oxide layer and probably tunnels through and/or is reflected by the oxide layer. The wave packet is deformed when it reaches the oxide layer. It is found that the higher the wave packet energy, the faster the wave packet moves and the higher the probability of transmitting the wave packet for the same bias voltage. It was also found that at low energy, the increase of bias voltage does not increase significantly the probability of finding the transmitted wave packet. At high energy, however, the probability of finding the transmitted wave packet becomes higher with increasing the bias voltage.